2020
DOI: 10.1055/s-0040-1710396
|View full text |Cite
|
Sign up to set email alerts
|

Perilunate Injury with Concomitant Short Radiolunate Ligament Disruption: Prevalence and Surgical Outcomes—"An Unusual Perilunate Injury Variant”

Abstract: Background In the classic description of perilunate injuries, the short radiolunate ligament (SRL) remains intact. Objective This study was aimed to determine the occurrence of SRL disruptions with perilunate injuries and review the clinical and radiographic outcomes after surgical management. Patients and Methods A retrospective review was conducted for patients who sustained a perilunate injury and a concomitant disruption of the SRL at a single–level-1 trauma center between January 2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…We present an unusual case of PLFD with acute ulnar nerve compression; to the best of our knowledge, this has only been previously reported in two case reports with two additional instances reported in cohort studies [ 9 , 10 , 11 , 12 ]. The fracture pattern is also rare, involving an atypical greater arc injury pattern in combination with an inferior arc injury.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We present an unusual case of PLFD with acute ulnar nerve compression; to the best of our knowledge, this has only been previously reported in two case reports with two additional instances reported in cohort studies [ 9 , 10 , 11 , 12 ]. The fracture pattern is also rare, involving an atypical greater arc injury pattern in combination with an inferior arc injury.…”
Section: Discussionmentioning
confidence: 78%
“…We present a case of PLFD in which the proximal scaphoid fragment dislocated volarly and ulnarly, causing acute compression of the ulnar nerve. Our review of the literature shows only four other reported cases of ulnar neuropathy in the setting of a PLFD and two cases of ulnar neuropathy in the setting of lunate dislocations [ 9 , 10 , 11 , 12 , 13 , 14 ]. Our patient also sustained a lunate facet distal radius fracture with radiocarpal subluxation, resulting in an exceedingly rare injury pattern involving both greater and inferior arc injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Это особенно важно, потому что клинические результаты ухудшаются при более длительном периоде наблюдения. В опубликованных исследованиях использовался тыльный [13], ладонный доступ [14] и комбинированный ладонный и тыльный доступ для восстановления всех поврежденных связок и разрыва капсул [15]. Также в некоторых исследованиях был использован артроскопический метод восстановления связочного аппарата [16; 17].…”
Section: результаты исследования и их обсуждениеunclassified